A full-field crystal-plasticity analysis of bimodal polycrystals. (February 2020) - Flipon, B.; Keller, C.; Quey, R.; Barbe, F.
Abstract: A full field crystal plasticity modelling of bimodal polycrystals is presented. Bimodal polycrystals are generated using a controlled Laguerre–Voronoi algorithm, and a modified phenomenological law is used to take into account the grain size effect through a Hall–Petch term. A focus is particularly made on the effects of grain size and of grain size ratio between ultrafine grains and coarse grains populations on local and global mechanical responses. The effect of the spatial distribution of the coarse grains (clustered or isolated) is also analysed in terms of strain localisation and stress concentration at the local scale.